AN ANALYSIS OF ENGLISH EDUCATION DEPARTMENT STUDENTS' ABILITY IN TOEFL READING COMPREHENSION - Solpia Nuraini; Winda Trisnawati; Ridho Kurniawan (Universitas Muhammadiyah Muara Bungo, 2022)
The TOEFL test is globally acknowledged as the foremost assessment tool for evaluating English proficiency levels (Warfield, 2013:133). This study explores the English department students' readiness for the TOEFL examination, with a specific focus on 4th-semester students enrolled in the TOEFL preparation class at STKIP MB. An observed issue pertains to reading comprehension difficulties encountered by students in this class. This difficulty primarily stems from the complexity and length of the texts, making it challenging to grasp the core ideas. Furthermore, students have been exposed to Academic Reading and Extensive Reading prior to the advanced Reading (TOEFL reading) section. This context demands specific skills such as extracting key ideas from passages, addressing direct and indirect questions, and enhancing vocabulary (Phillips, 2001). This research identifies a link between reading comprehension and reading techniques. Patel and Jain (2008:80) distinguish intensive, extensive, Aloud, and Silent reading techniques, with students struggling to maintain focus and comprehend texts effectively. Inefficient strategies often lead to time-consuming responses to reading comprehension questions. Another significant hurdle is that students tend to read passages word by word, hindering their ability to retain information. Harmar (2018:25) aptly notes,